The role of banks in monitoring firms : the case of the Crédit Mobilier - Paulet, Elisabeth, 1962- (Routledge explorations in economic history., 2002)
This book addresses issues in the current literature on corporate finance using historical evidence. In particular it looks at the role of universal banks in relaxing the credit constraints of firms, supervising managers and stabilizing share prices. The key issues is whether the Anglo-American asset based financing is more effective than the main-bank approach used in Germany and Japan. Earlier studies have found that firms with a close relationship with a major bank have high market value compared to book value, although it is difficult to determine whether this is cause or effect.